Efektivitas Tradisi Kowea Tabako pada Masyarakat Wawonii di Desa Rawa Indah Kecamatan Wawonii Tengah Kabupaten Konawe Kepulauan - Resna Wati; Ahmat Keke; Hidayah Rahman (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2023)
Kowea Tabako is a traditional oral invitation owned by the Wawonii community, which uses cigarettes as the medium for its implementation. Kowea Tabako interprets the Wawonii community as a form of appreciation for relatives who will be invited. The purpose of this study was to find out and describe the implementation of the Kowea Tabako tradition, and the effectiveness of Kowea Tabako in the Wawonii community in Rawa Indah Village, Central Wawonii District. Data collection was carried out using observation techniques and in-depth interviews. The data obtained were analyzed by descriptive qualitative. This research shows that Kowea Tabako already existed during the Dingge (Kingdom) era. Kowea Tabako in the Wawonii Community has a unique process, in practice using objects such as cigarettes, and matches which are placed on a plate and wrapped in a handkerchief brought by the invitee to be served to the families who will be invited. Verbal invitations to use a cigarette (tobacco) as a symbol of appreciation, a match (ticks) as a symbol of blessing, a plate (kungfu) as a small traditional symbol, and a white handkerchief as a symbol of purity. so that the invited relatives feel heavy-hearted if they do not attend the event. Kowea Tabako serves to hide as well as invite families to attend an event. Kowea Tabako has a meaning as a form of appreciation and honor in inviting family, and the one who is given the mandate to bring Kowea Tabako is a man.